Implementation of Online Learning Model in Class X of Senior High School during COVID-19 - Kusuma Wardany; Sulis Anjarwati; Muhammad Hadziq Qulubi (Universitas Muhammadiyah Mataram, 2021)
The purpose of this research is to find out how to implement online learning models and to find out what factors hinder the implementation of online learning. This research method uses qualitative research methods with descriptive analysis techniques. This analysis technique is obtained from the results of observations, interviews and the field by means of data collection, data reduction, data presentation, conclusions and verification. The number od student in class X is 30 people. The results of this study indicate that the implementation of online learning models, especially in class X students, is by utilizing several kinds of applications and the factors that hinder the implementation of online learning are the lack of effectiveness and time efficiency, lack of student interest and lack of understanding of the material. The positive impact of online learning is that the learning model applied by teachers is considered quite effective. Because the teacher uses instructional videos, written assignments and practices.